A rare case of toxocariasis presenting with hypereosinophilic pericardial effusion and mycotic aneurysm. (January 2022) - Sandal, Sapna; Krishnan, Gopal; Sharma, Ashish; Ismail, Javed; Yadav, Jaivinder
Parasitic infections are the leading cause of hypereosinophilia in the paediatric population in tropical countries. We report an unusual case of Toxocara infection in an eight-year-old boy who presented with intermittent fever, hypereosinophilia complicated by massive pericardial effusion and a mycotic aneurysm. This child received treatment with four weeks of albendazole and steroids.